Emerging roles of FOXK2 in cancers and metabolic disorders - Xing, Xiaoke; Que, Xiangyong; Zheng, Sihao; Wang, Shuxian; Song, Qibin; Yao, Yi; Zhang, Pingfeng (Frontiers in Oncology, 2024)
FOXK2, a member of the Forkhead box K (FOXK) transcription factor family, is widely expressed in various tissues and organs throughout the body. FOXK2 plays crucial roles in cell proliferation, differentiation, autophagy, de novo nucleotide biosynthesis, DNA damage response, and aerobic glycolysis. Although FOXK2 is recognized as an oncogene in colorectal cancer and hepatocellular carcinoma, it acts as a tumor suppressor in breast cancer, cervical cancer, and nonsmall cell lung cancer (NSCLC). This review provides an overview of the recent progress in understanding the regulatory mechanisms of FOXK2 and its downstream targets, highlights the significant impact of FOXK2 dysregulation on cancer etiology, and discusses the potential of targeting FOXK2 for cancer treatment.